2014
DOI: 10.1371/journal.pone.0099560
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Relationship between Hotspots and Recombination Associated with Chromosome 21 Nondisjunction

Abstract: Trisomy 21, resulting in Down Syndrome (DS), is the most common autosomal trisomy among live-born infants and is caused mainly by nondisjunction of chromosome 21 within oocytes. Risk factors for nondisjunction depend on the parental origin and type of meiotic error. For errors in the oocyte, increased maternal age and altered patterns of recombination are highly associated with nondisjunction. Studies of normal meiotic events in humans have shown that recombination clusters in regions referred to as hotspots. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
(29 reference statements)
3
32
0
Order By: Relevance
“…Very recently, Oliver et al [30] has analyzed the molecular features and distribution of recombination hotspots along the length of nondisjoined Ch21 to get more insight on the relationship between recombination and Ch21 NDJ. Studies of normal meiotic events in humans show that the placement of recombination is not a random event.…”
Section: Recombination Hotspots and Their Relationship With Ch21 Ndjmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Oliver et al [30] has analyzed the molecular features and distribution of recombination hotspots along the length of nondisjoined Ch21 to get more insight on the relationship between recombination and Ch21 NDJ. Studies of normal meiotic events in humans show that the placement of recombination is not a random event.…”
Section: Recombination Hotspots and Their Relationship With Ch21 Ndjmentioning
confidence: 99%
“…In addition, sequence variation in the zinc-finger domain of the gene Proline Rich Domain Containing 9 (PRDM9) has a major impact on the location of recombination in humans [32]. The observation that both cis and trans-acting factors are associated with the placement of recombination led authors to enquire whether the altered patterns of recombination associated with NDJ of Ch21 could be explained by differences in the relationship between recombination and genomic features (i.e., GC content, CpG fraction, Poly(A)/Poly(T) fraction or gene density) on 21q or differential hot-spot usage [30].…”
Section: Recombination Hotspots and Their Relationship With Ch21 Ndjmentioning
confidence: 99%
See 1 more Smart Citation
“…Nondisjunction of chromosome 21 in particular is known as Down syndrome, which easily causes infertility, abortion and chromosomal abnormalities (1)(2)(3). Folic acid (FA) is a water-soluble vitamin, which is an essential nutrient for normal cell growth, fetal development (4), methylation (5) and DNA stability (6).…”
mentioning
confidence: 99%
“…Wang et al (9) reported that when human lymphocytes were incubated in a low-FA medium, there was an increase in aneuploidy of chromosome 21. Meanwhile Takamura et al (2) and Oliver et al (3) reported that mothers of Down syndrome children have lower serum and plasma FA levels than mothers of non-Down syndrome children. James et al (10) reported that there were increased levels and frequencies of homocysteine in plasma and methylenetetrahydrofolate reductase (MTHFR) 677CT and 677TT genotypes in mothers of Down syndrome children, respectively.…”
mentioning
confidence: 99%